A piacgazdaság és a civil társadalom térbeli dimenziói - Timár, Lajos (Tér és Társadalom, 1990)
Settlement geographical functions of certain settlements have their social "dimensions": We can also put it this way: factors analyzed by settlement geography as local, central or specific settlement functions, and of these especially the central or urban basic functions, the level and composition of higher service functions influence the chances of reproduction of not only the economic, but also the cultural and symbolic capital. If we reflect Bourdieu's capital concept to the level of settlement network we can say that economic, cultural and symbolic capitals are distributed unevenly not only among different social groups and strata, but also among different settlements. The settlement-specific characteristics of the interrelationship among economic, cultural and symbolic capitals at different levels of settlement hierarchy should be analyzed separately. It is also evident that the "historic rhythm" of the reproduction of the three different kinds of capital is different at national level, and the intensity the different types of capital join the international division of labour is also different. Capitalism as an international, world system can be characterized by the asymetric reproduction of not only the economic, but also the cultural and symbolic capitals as well. Asymetric character appears at national level as well: we think, that in the case of smaller countries not so much at regional, but rather at settlement levels. As "historical differences are the products of the historical dialectics of cumulative differences", the rhythm of reproduction of economic capital in certain settlements might be completely different from that of the cultural capital.